Lançamento oblíquo: uma abordagem matemática - Almeida, Francisco Fabio Monteiro de (2016)
The main goal of this work is to verify that we can assign the oblique launch a mathematical approach. To reach this conclusion, we address important issues of mathematics and physics, as linear functions and quadratic functions , and uniform and uniformly varied movements. These concepts were presented to facilitate understanding and implement an equation that allows to determine the moment of rise, the maximum height and horizontal reach, knowing an shot's angle, the initial velocity and gravity's acceleration.